Proteomic profiling of human plasma identifies apolipoprotein E as being associated with smoking and a marker for squamous metaplasia of the lung. Issue 18 (3rd July 2015) - Rice, Shawn J.; Liu, Xin; Miller, Bruce; Joshi, Monika; Zhu, Junjia; Caruso, Carla; Gilbert, Chris; Toth, Jennifer; Reed, Michael; Rassaei, Negar; Das, Arun; Barochia, Amit; et al.
Abstract : Biomarkers to identify subjects at high‐risk for developing lung cancer will revolutionize the disease outlook. Most biomarker studies have focused on patients already diagnosed with lung cancer and in most cases the disease is often advanced and incurable. The objective of this study was to use proteomics to identify a plasma biomarker for early detection of lung lesions that may subsequently be the harbinger for cancer. Plasma samples were obtained from subjects without lung cancer grouped as never, current, or ex‐smokers. An iTRAQ‐based proteomic analysis was performed on these pooled plasma samples. We identified 31 proteins differentially abundant in current smokers or ex‐smokers relative to never smokers. Western blot and ELISA analyses confirmed the iTRAQ results that demonstrated an increase of apolipoprotein E (APOE) in current smokers as compared to both never and ex‐smokers. There was a strong and significant correlation of the plasma APOE levels with development of premalignant squamous metaplasia. Additionally, we also showed that higher tissue levels of APOE are seen with squamous metaplasia, supporting a direct relationship. Our analysis reveals that elevated plasma APOE is associated with smoking, and APOE is a novel predictive protein biomarker for early morphological changes of squamous metaplasia in the lung.